2009
DOI: 10.1093/ndt/gfp041
|View full text |Cite
|
Sign up to set email alerts
|

Blocking adenosine A2A receptor reduces peritoneal fibrosis in two independent experimental models

Abstract: Our data suggest that adenosine through its A(2A)R promotes peritoneal fibrosis and therefore should be considered as a target for pharmacological intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…This latter finding might account for the well-documented observation that coffee drinking and caffeine ingestion reduces deaths from liver disease 145-149 . Peritoneal fibrosis also depends on A 2a stimulation in animal models 150 . In the setting of priapism, in which the chronically engorged penis becomes hypoxic, adenosine release leads to both vasodilation and fibrosis via activation of A 2b 151,152 .…”
Section: Adenosine Receptors and Fibrosismentioning
confidence: 99%
“…This latter finding might account for the well-documented observation that coffee drinking and caffeine ingestion reduces deaths from liver disease 145-149 . Peritoneal fibrosis also depends on A 2a stimulation in animal models 150 . In the setting of priapism, in which the chronically engorged penis becomes hypoxic, adenosine release leads to both vasodilation and fibrosis via activation of A 2b 151,152 .…”
Section: Adenosine Receptors and Fibrosismentioning
confidence: 99%
“…Peritoneal fibrosis is a common complication of chronic peritoneal dialysis or surgery and may lead to diminished efficacy of peritoneal dialysis, development of intestinal adhesions, and obstruction. Recent work indicates that either pharmacological blockade or deletion of ADO A 2A receptors can diminish peritoneal fibrosis (109). In contrast, others have reported that topical application of ADO and phosphorylated ADO derivatives could, by acting via ADO receptors, diminish peritoneal adhesions in a rodent model (110).…”
Section: Modulation Of Peritoneal and Cardiac Fibrosis By Adomentioning
confidence: 99%
“…These results also parallel those findings of murine models of cirrhosis and peritoneal fibrosis in which adenosine A 2A receptor antagonism also has been observed to be beneficial. 23,31 TGF-β is cytokine produced and released by platelets, fibroblasts, and endothelial, epithelial, and inflammatory cells, such as macrophages and lymphocytes, after a wound occurs. TGF-β participates in the regulatory process of cell proliferation, with an important role in tissue repair, and has been linked to the formation of hypertrophic scars and keloids in a number of ways.…”
Section: Discussionmentioning
confidence: 99%